The effect of Styrene Maleic Anhydride on the microstructure evolution of PSF-based membrane prepared by thermal-induced phase separation method. (December 2019) - Tesha, John Michael; Dlamini, Derrick S.; Cui, Zhenyu; Li, Jianxin
Highlights: Microporous PSF/SMA membrane was prepared via TIPS method. Use of nontoxic to human-life DPGDB solvent to dissolve PSF and SMA during membrane preparation. SMA improved membrane pore size and porosity. Because of SMA, membranes became fouling resistant. Higher SMA loading compromised mechanical stability. Abstract: Polysulfone (PSF) and Styrene Maleic Anhydride (SMA) were blended by thermally induced phase separation method in the preparation of membranes for water treatment. Dipropylene Glycol Dibenzoate (DPGDB) was used as a diluent which was extracted using ethanol. The increase in SMA concentration was positively confirmed by monitoring the intensity of the peak at 1779 cm −1 characteristic to CO in the Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR) spectra. This observation was validated by elemental quantification using X-Ray Photoelectron Spectroscopy (XPS). Scanning Electron Microscopy (SEM) showed that the surface and cross-section morphology changed with an increase in SMA concentration. The average membrane pore size increased from 38.25 nm to 61.30 nm. In the same regard, average porosity increased from 16% to 57%. These observations were attributed to the effect of SMA molecules on the liquid-solid phase separation. The effect of SMA on wettability of the membrane was investigated by contact angle measurements where it was found that the hydrophilicity decrease with an increase in SMA content. The hydrophilicity had positive influence in membrane fouling resistance. The antifouling propensity reached up to 91% when the SMA content was 2% wt/wt compared to the base membrane which was 86%. The maximum pure water flux was found to be 147 Lm −2  h −1 when the SMA content was 2%. It decreases to 33 Lm −2  h −1 when SMA increases to 10% wt/wt. On the other hand, Bovine Serum Albumin (BSA) rejection increased with an increase in SMA concentration. The highest rejection was 92 ± 3%.